Alcohol control policy and changes in alcohol‐related traffic harm. (3rd October 2019) - Rehm, Jürgen; Manthey, Jakob; Lange, Shannon; Badaras, Robertas; Zurlyte, Ingrida; Passmore, Jonathon; Breda, João; Ferreira‐Borges, Carina; Štelemėkas, Mindaugas
Abstract: Aims: To study the impact of alcohol control policy measures (i.e. increases in taxation, restrictions on availability, including minimum purchasing age regulations, legislation on drink driving and advertisement bans) on alcohol‐related traffic harm in Lithuania between January 2004 and February 2019. Design: Analyses of trend data on the proportion of alcohol‐related collisions and crashes, injury and mortality, adjusting for secular trends, seasonality, periods of alcohol control measure implementation and economic development. Generalized additive mixed models were used. Multiple sensitivity analyses were conducted. Setting: Lithuania. Cases: Monthly number of alcohol‐related cases of traffic collisions and crashes, injuries and deaths. Interventions and comparators: Periods of time during which new alcohol control measures were implemented and/or augmented compared to periods when they were not. Measurements: Monthly data for 2004 to 2019 from routine statistics of the Lithuanian Road Police Service. Findings: All indicators decreased consistently and significantly after the implementation of alcohol control measures, including increased taxation, reduction of availability and a ban on advertisement, starting in 2014. On average, each implemented policy measure permanently reduced the proportion of alcohol‐attributable crashes by 0.55% [95% confidence interval (CI) = 0.21–0.90%; P = 0.002], the proportion of alcohol‐attributable injuries by 0.60% (95% CI = 0.24–0.97%; P = 0.001) and the proportion of alcohol‐attributable deaths by 0.13% (95% CI = 0.10–0.15%; P < 0.001). Conclusions: Alcohol control policy measures, including measures to reduce overall level of alcohol consumption, were associated with a marked decrease in alcohol‐related traffic harm.